Public Relations dan Masyarakat dalam Memacu Pertumbuhan Pariwisata - Yuanita Safitri (Bina Nusantara University, 2015)
Tourism is an important determinant for a region’s economic growth—the higher income from tourism, the higher its gross regional domestic product. To be successful in exposing potential tourism sites, a region does not only depend on the beauty of the nature but also how to access the sites, on-site accommodation and the mutual relationship between local government and local community.The fact is many regions have difficulties in developing mutual relationship between local government and local community. It means what most important is how the tourism industry is being managed. One most important aspect of managing the tourism industry is the cooperation and communication between the local community and the government. This article aims to discuss how public relations and the local community work to stimulate tourism growth in a synergy. Using descriptive qualitative method, this article recommends a model of communication strategy—in which the local community serves mainly as the tourism’s public relation agents, and also serves as a reference method in evaluating a local government’s communication strategies in regional tourism industry.